Spatial and temporal relationships between deer harvest and deer–vehicle collisions at Oak Ridge Reservation, Tennessee - Lisa I. Muller; Amanda M. Hackworth; Neil R. Giffen; James W. Evans; Jason Henning; Graham J. Hickling; Phillip Allen (Wildlife Society Bulletin)
ABSTRACT White‐tailed deer (Odocoileus virginianus)–vehicle collisions (DVCs) are increasing as human and deer populations continue to grow. Deer harvest was implemented at Oak Ridge Reservation, Tennessee (ORR) in 1985 to reduce DVCs. We assessed the relationship between DVCs at ORR to deer harvest, road type, and habitat features (forest, field, water, and developed cover types) during 1986–2008 using Poisson regression analysis and Akaike Information Criterion modeling. We also evaluated DVC numbers for the city of Oak Ridge and ORR during 1975–2008 to examine the effects of moon phase, employee work‐shift timing, and season on DVCs. From 1975 to 2008, 4,637 DVCs occurred in Oak Ridge and ORR, with monthly DVCs peaking each November. Most DVCs occurred at the start of the workday. Annual DVC totals peaked at 273 in 1985; deer harvest was then implemented and DVCs declined. No harvest occurred in 2001 and DVCs increased for the next 2 years. A model including harvest, road type and distance, development, and water features received full support for explaining DVC occurrence. Harvest in the previous year was positively related to DVCs, likely reflecting higher hunter success with higher deer density. Higher traffic volume and speed were positively related to DVCs. There was no effect of moon phase for all records combined; however, analysis by season and gender showed a positive relationship to collisions for male deer during the gestation period (1 Jan–14 May), which may have been associated with dispersal. We recommend continued deer harvest and driver education to reduce DVCs. © 2014 The Wildlife Society.